The Influence of Online Games on a Person’s Emotions - Feyzal Rizkillah; Dewi Khurun Aini; Ikhrom, Ikhrom (Jurnal Multidisiplin Sahombu, 2025)
This study examines the emotional effects of online gaming on teenagers and young adults, emphasizing both the beneficial and improvement of cognitive abilities, and social interaction via multiplayer platforms. Nonetheless, excessive gaming has been linked to emotional instability, such as anger problems, depression, anxiety, and social withdrawal. Employing a qualitive phenomenological method with purposive sampling, the research conducted interviews and observation of gamers aged 13 to 25 who engage in online gaming for over an hour each day. Result indicates that the release of dopamine from accomplishments in games promotes addictive behavior, leading to extended playtime even in the face of emotional turmoil. Anger problems frequently arise from a sense of loss, injustice, dan placing blame outside oneself instead of engaging in self reflection. The study uses behaviorist theory to analyze the stimulus-response connection related to gaming addiction and emotional reaction, highlighting the importance of personalized interventions. In the end, encouraging a balanced gaming strategy can enhance advantages, while reducing psychological threats for at-risk young people.